2020
DOI: 10.3390/nu12061896
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3-Month Astaxanthin Supplementation on Cardiac Function in Heart Failure Patients with Left Ventricular Systolic Dysfunction-A Pilot Study

Abstract: Astaxanthin has strong antioxidant properties. We conducted a prospective pilot study on heart failure (HF) patients with left ventricular (LV) systolic dysfunction to investigate improvements in cardiac function and exercise tolerance in relation to suppression of oxidative stress by 3-month astaxanthin supplementation. Oxidative stress markers—serum Diacron reactive oxygen metabolite (dROM), biological antioxidant potential (BAP), and urinary 8-hydroxy-2′-deoxyguanosine (8-OHdG) concentrations, LV ejection f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…This process reduces the generation of mitochondrial superoxide, reduces telomere shortening [30] . This shows that the mitochondrial production of ROS acts as one of the causes of replicative senescence [45] . Passos et al also reported that by classifying early senescent cells from cultures of young proliferating fibroblasts, they showed that these cells have higher ROS levels, dysfunctional mitochondria, and shorter telomeres.…”
Section: Astaxanthin As Antioxidant and Antiinflammatorymentioning
confidence: 96%
See 1 more Smart Citation
“…This process reduces the generation of mitochondrial superoxide, reduces telomere shortening [30] . This shows that the mitochondrial production of ROS acts as one of the causes of replicative senescence [45] . Passos et al also reported that by classifying early senescent cells from cultures of young proliferating fibroblasts, they showed that these cells have higher ROS levels, dysfunctional mitochondria, and shorter telomeres.…”
Section: Astaxanthin As Antioxidant and Antiinflammatorymentioning
confidence: 96%
“…By observing the effects of AXT in the control of many inflammatory processes, its therapeutic potential involving MS were observed in this review. The study by Kato et al (2020) showed that the administration of 12mg of ATX decreased the oxidative stress in the serum marker Diacron reactive oxygen metabolite (dROM) in heart failure patients, although the urinary marker 8-hydroxy-2′deoxyguanosine (8-OHdG) did not present significant changes [48] . On the other hand, the randomized study by demonstrated that the administration of 8mg of ATX for 8 weeks in human health female dramatically reduced DNA damage biomarker 8-OHdG as well as the blood inflammatory marker C-reactive protein (CRP) [49] .…”
Section: Astaxanthin and Metabolic Syndromementioning
confidence: 99%
“…In addition, regular consumption of ASX led to a significant decrease in the levels of LDLcholesterol and apolipoprotein B [12]. A pilot clinical study conducted by Kato et al [24] on 16 patients with a risk of heart failure who were taking 12 mg of ASX supplementation daily for 3 months [24]. Researchers have assessed 6-min walk distance, blood pressure, BMI, left ventricular ejection fraction, heart rate, and numerous oxidative stress markers, including urinary 8-hydroxy-2-deoxyguanosine, biological antioxidant potential, and the diacron-reactive oxygen metabolites (d-ROM).…”
Section: Cardiovascular Health Diseasesmentioning
confidence: 99%
“…microalgae, crayfish, salmon, and shrimp) and is known for its powerful antioxidant, immunomodulatory, anti-inflammatory, and anti-fibrotic properties ( Landon et al, 2020 ). The cardioprotective effects of ASX have been reported in humans and animals ( Fassett and Coombes, 2011 , Fassett and Coombes, 2012 , Kato et al, 2020 ). In this review, 3-months supplementation of ASX to patients with HF improved the LV ejection fraction (LVEF), extended their 6-min walking distance, and decreased markers of oxidative stress ( Kato et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The cardioprotective effects of ASX have been reported in humans and animals ( Fassett and Coombes, 2011 , Fassett and Coombes, 2012 , Kato et al, 2020 ). In this review, 3-months supplementation of ASX to patients with HF improved the LV ejection fraction (LVEF), extended their 6-min walking distance, and decreased markers of oxidative stress ( Kato et al, 2020 ). Also, ASX prevented cardiac muscle damage and preserved left ventricular LV function after heavy exercise, ischemia/reperfusion, and myocardial infarction (MI)-induced cardiac injury by suppressing oxidative stress and inflammation ( Adluri et al, 2013 , Aoi et al, 2003 , Gross and Lockwood, 2004 , Gross and Lockwood, 2005 ).…”
Section: Introductionmentioning
confidence: 99%